Binder composition and preparation method thereof, pole piece, battery containing pole piece and electric device
By using the composition of the first adhesive and the second adhesive in the battery electrode sheet, the synergistic effect of linear and dot bonding is achieved, and the problem of poor stability and consistency of the electrode sheet caused by a single adhesive is solved, which significantly improves the stability of the battery capacity and the development potential of high-capacity batteries.
Patent Information
- Application Number
- CN202311426706.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The single binder commonly used in existing battery pole sheets cannot effectively combine conductive substances and active substances, resulting in poor stability and consistency of the pole sheet, which in turn affects the stability of battery capacity and the development of high-capacity batteries.
Using an adhesive composition including a first adhesive and a second adhesive, the first adhesive produces a linear bond through fibrosis, and the second adhesive cooperates with the first adhesive through dot bonding to improve the bond strength and cohesion energy.
It significantly improves the stability and consistency of the pole sheet, reduces "powder loss" and cracking, improves the stability of battery capacity, and supports the development of high-capacity batteries.
Smart Images

Figure CN119912903A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a binder composition and a preparation method thereof, a pole piece, a battery and an electrical device comprising the same. Background Art
[0002] At present, a single binder is usually used in electrode materials to bind conductive materials and active materials to the current collector. However, the single binder has a single mode of action with conductive materials and active materials, mainly in the form of embedding small particles or covering with filament-like materials, and fails to organically combine these two modes of action, resulting in problems such as "powder loss" and cracking in the pole piece, which in turn causes problems such as poor stability and consistency of the pole piece, resulting in battery capacity attenuation and limiting the development of high-capacity batteries.
[0003] Therefore, there is a need to improve the adhesive, which can provide improved bonding effect, thereby facilitating the stability of pole piece molding and further improving the stability of battery capacity. Summary of the invention
[0004] This application is made in view of the above-mentioned problems, and aims to provide an adhesive composition comprising a first adhesive and a second adhesive, wherein the point bonding of the second adhesive and the linear bonding of the first adhesive are organically combined to achieve a synergistic bonding effect, greatly improve the bonding strength and cohesive energy, and thus improve the stability and consistency of the pole piece. This application also provides a preparation method of the above-mentioned adhesive composition, as well as a corresponding pole piece, a battery and an electrical device.
[0005] In order to achieve the above object, the first aspect of the present application provides a binder composition, the binder composition comprising:
[0006] a first binder; and
[0007] A second binder, wherein the second binder comprises a hyperbranched polymer obtained by polymerization of monomer A and monomer B;
[0008] Wherein, the monomer A comprises at least one of the compounds represented by general formula (I):
[0009]
[0010] Wherein, R1, R2, R3 are each independently selected from -H or R4 is selected from -H, -OH, -CH2OR 1a , -C1-C3 alkyl or and R1, R2, and R3 are not all -H at the same time, and when two of R1, R2, and R3 are selected from -H, R4 is selected from Each R 1a , R1b , R 1c Each is independently selected from -H or -C1-C4 alkyl, and n is an integer from 0 to 5;
[0011] The monomer B includes at least one of the compounds represented by general formula (II):
[0012]
[0013] wherein Ra and Rb are each independently selected from -H, -C1-C3 alkyl or -COOR'; Rc is selected from -COOR', -CON(R')2 or Wherein R' is independently selected from -H, -C1-C6 alkyl or -(CH2) m -OH; m is an integer of 1 to 5.
[0014] In the bonding process of the adhesive composition of the present application, the first adhesive produces fibrillated linear bonding, and the second adhesive provides point bonding at the same time, and the two cooperate with each other and interact with each other, thereby producing a synergistic bonding effect. In addition, the second adhesive includes a hyperbranched polymer obtained by polymerization of monomer A and monomer B, which includes a large number of polar groups, thereby having good electronegativity, which is conducive to promoting the formation of a conductive network and improving the power density of the electrode. On the other hand, the presence of the hyperbranched structure makes the adhesive highly elastic, further improves the flexibility of the pole piece, not only facilitates processing, but also buffers the large volume changes of the active material, so that the pole piece maintains integrity and stability during long-term cycles.
[0015] According to any embodiment, in the general formula (I), R1, R2, and R3 are each independently selected from and R4 is selected from -OH, -CH2OR 1a , -CH2CH3 or Each R 1a , R 1b , R 1c Each is independently selected from -H, -CH3 or -CH2CH3, and n is 0 or 1. Without wishing to be limited by theory, the monomers of the above-defined general formula (I) and general formula (II) can more easily obtain branched polymers with appropriate molecular weight, appropriate degree of branching and appropriate degree of dispersion through free radical polymerization.
[0016] According to any embodiment, in the general formula (II), Ra is selected from -H, Rb is selected from -H or -C1-C3 alkyl; Rc is selected from -COOR' or wherein R' is selected from -H, -C1-C4 alkyl, -CH2OH or -CH2CH2OH.
[0017] Without wishing to be limited by theory, the monomers of the above-defined general formula (II) and general formula (I) can more easily obtain branched polymers with appropriate molecular weight, appropriate degree of branching and appropriate degree of dispersion through polymerization.
[0018] According to any embodiment, the monomer A includes at least one of pentaerythritol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate or ethoxylated pentaerythritol tetraacrylate. These monomer raw materials are cheap and easy to obtain, so that the second binder can be obtained at a relatively low cost, thus being suitable for large-scale commercial production.
[0019] According to any embodiment, the monomer B includes at least one of acrylic acid, methacrylic acid, N-vinyl pyrrolidone, methyl methacrylate, ethyl methacrylate, propyl methacrylate, hydroxyethyl methacrylate or butyl methacrylate. Similarly, these monomer raw materials are cheap and easy to obtain, so that the second binder can be obtained at a lower cost, which is suitable for large-scale commercial production.
[0020] According to any embodiment, the molar ratio of the monomer A to the monomer B is 1:2-4, and can be 1:2-3. The molar ratio of the monomer A to the monomer B affects the viscosity, flexibility, etc. of the obtained branched polymer. When it is within the range of the present application, the obtained branched polymer has a low viscosity, is easy to process, and has moderate flexibility.
[0021] According to any embodiment, the number average molecular weight of the second binder is 100,000 to 1,000,000. In this article, the term "number average molecular weight" refers to the sum of the product of the molecular weight of all molecules in the polymer and the number fraction thereof. The number average molecular weight of the binder is within this range, so that the formed branched polymer has a moderate degree of branching and plays an effective point bonding role; and the viscosity is moderate, which is conducive to subsequent processing and production, especially conducive to forming small particle size powder in spray drying.
[0022] According to any embodiment, the first binder is not particularly limited, as long as its powder can be fibrillated under shear force and play a role in linear bonding. In any embodiment, the first binder includes at least one of PTFE-based binders, PVDF-based binders, modified PVDF-based binders, polyacrylonitrile (PAN)-based binders, styrene-butadiene rubber (SBR), and polyacrylamide (PAM). These first binders are all cheap and easy to obtain, so the binder composition of the present application can be obtained at a relatively low cost.
[0023] According to any embodiment, the mass ratio of the first binder to the second binder is (0.1-9.9):(9.9-0.1), and can be optionally (3-7):(7-3). The combination of the first binder and the second binder within this range can achieve a synergistic bonding effect by the fibrillated linear bonding of the first binder and the point bonding of the second binder itself, thereby improving the bonding strength and cohesion during pole piece molding.
[0024] According to any embodiment, the volume average particle size Dv50 of the binder composition is 5 μm-50 μm, and optionally 5 μm-10 μm. In the powder form within this range, the active material and the conductive material can be effectively combined on the current collector.
[0025] The second aspect of the present application also provides a method for preparing the binder composition as described above, the method comprising:
[0026] providing a first adhesive;
[0027] polymerizing a mixture including monomer A and monomer B to obtain a second binder; and
[0028] mixing the first binder and the second binder;
[0029] Wherein, the second binder comprises a hyperbranched polymer obtained by polymerization of monomer A and monomer B;
[0030] Wherein, the monomer A comprises at least one of the compounds represented by general formula (I):
[0031]
[0032] Wherein, R1, R2, R3 are each independently selected from -H or R4 is selected from -H, -OH, -CH2OR 1a , -C1-C3 alkyl or and R1, R2, and R3 are not all -H at the same time, and when two of R1, R2, and R3 are selected from -H, R4 is selected from Each R 1a , R 1b , R 1c Each is independently selected from -H or -C1-C4 alkyl, and n is an integer from 0 to 5;
[0033] The monomer B includes at least one of the compounds represented by general formula (II):
[0034]
[0035] Wherein, Ra and Rb are each independently selected from -H, -C1-C3 alkyl or -COOR'; Rc is selected from -COOR', -CON(R')2 or Wherein R' is independently selected from -H, -C1-C6 alkyl or -(CH2) m -OH; m is an integer from 1 to 5. The preparation method according to the present application has low raw material cost and is suitable for industrial production.
[0036] As described in the first aspect, the first binder is not particularly limited, as long as its powder can be fibrillated under the action of shear force and function in a linear bonding manner. In any embodiment, the first binder includes at least one of a PTFE-based binder, a PVDF-based binder, a modified PVDF-based binder, a polyacrylonitrile (PAN)-based binder, styrene-butadiene rubber (SBR), and a polyacrylamide (PAM).
[0037] The third aspect of the present application provides an electrode plate, comprising: a current collector and an electrode film layer arranged on at least one side of the current collector, the electrode film layer comprising the binder composition of the first aspect of the present application, or a binder composition prepared according to the method of the second aspect of the present application.
[0038] According to any embodiment, the electrode plate is a positive electrode plate and / or a negative electrode plate. Generally speaking, when the first binder used is suitable for a positive electrode plate, the electrode plate provided in this application is used as a positive electrode plate; when the first binder used is suitable for a negative electrode plate, the electrode plate provided in this application is used as a negative electrode plate, but is not limited thereto.
[0039] The fourth aspect of the present application provides a battery, comprising a pole piece selected from the third aspect of the present application.
[0040] The fifth aspect of the present application provides an electrical device, comprising the battery of the fourth aspect of the present application.
[0041] The binder composition provided in the present application, by combining the first binder and the second binder, can achieve the synergistic bonding effect of linear bonding and point bonding when applied to the electrode material, thereby improving the bonding strength and cohesive energy, thereby improving the stability and consistency of the pole piece, and improving the "powder falling" and cracking phenomenon in the pole piece. In addition, the branched structure included in the second binder can promote its own polar groups (such as carbonyl and ester groups) to better form stable hydrogen bonds with substances such as conductive agents, and at the same time, the cross-linked structure can better resist the expansion of the electrode. In addition, the binder composition of the present application is provided in the form of a powder, without the use of solvents such as NMP, which is more environmentally friendly and cost-effective. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1Schematic diagram of a cross-linked network of a binder according to one embodiment of the present application.
[0043] Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0044] Figure 3 yes Figure 2 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0045] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0046] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0047] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0048] Figure 7 Schematic diagram of an electrical device using a battery as a power source according to an embodiment of the present application.
[0049] Description of reference numerals:
[0050] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0051] Below, the negative electrode plate and its manufacturing method, battery and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0052] "Scope" disclosed in the present application is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following range can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0 to 5" means that all real numbers between "0 to 5" are listed in this document, and "0 to 5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0053] In the present application, the term "alkyl" includes straight chain, branched and cyclic alkyl. Examples of alkyl include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, n-butyl, pentyl, hexyl, etc. The term "alkyl" includes unsubstituted alkyl and substituted alkyl. The term "C1-Cn alkyl" (wherein n is an integer from 2 to 6) represents an alkyl having 1 to "n" carbon atoms. In some embodiments, for example, the alkyl can be substituted by groups such as hydroxyl, amino, halogen, carboxyl, carboxylate, amide, carbamate or aminoalkyl.
[0054] In this application, the groups appearing in is the site of attachment of a group / moiety. For example, Indicates that the group is connected to other groups / parts through a nitrogen atom, This means that the moiety is connected to other groups / moieties through an oxygen atom.
[0055] In this application, the term "particle size" refers to the expression Dv50, that is, the particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 50%. If not specifically limited, the particle size of the binder in this application is determined by a laser particle size analyzer (such as Malvern Master Size 3000).
[0056] In this application, when the "molecular weight" of a polymer is mentioned, it means the number average molecular weight. If not specifically limited, the number average molecular weight of the adhesive of this application is determined by gel permeation chromatography. For example, a Waters 2695IsocraticHPLC gel chromatograph (differential refractive index detector 2141) is used for testing. In some embodiments, the test method is to use a polystyrene solution sample with a mass fraction of 3.0% as a reference and select a matching chromatographic column (oily: StyragelHT5DMF7.8*300mm+StyragelHT4). A 3.0% adhesive glue is prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution is allowed to stand for one day for standby use. During the test, tetrahydrofuran is first drawn with a syringe, rinsed, and repeated several times. Then 5 ml of the experimental solution is drawn, the air in the syringe is removed, and the needle tip is wiped dry. Finally, the sample solution is slowly injected into the injection port. After the indication is stable, data is obtained and the number average molecular weight is read.
[0057] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0058] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0059] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0060] In the field of batteries, the widely used polymer binders are mainly in the form of linear molecular chains, and the bonding performance is mainly based on intermolecular forces, which will inevitably lead to insufficient bonding between the binder and the active substance and conductive carbon material, resulting in powder loss and low cohesive strength. Moreover, most linear molecular chains have an inevitable swelling process, which leads to cracking of the pole piece. In addition, the single binder has a single form of action with the conductive material and the active material, mainly in the form of small particles embedded, or covered with a filament-like material, and it is impossible to organically combine these two effects, which will also lead to problems such as powder loss and cracking in the pole piece, and then cause problems such as poor pole piece consistency and battery capacity attenuation, limiting the development of high-capacity batteries. In addition, existing polymer binders usually require solvents, such as NMP, when used.
[0061] In view of this, the present inventors propose a binder composition and a preparation method thereof, an electrode plate, a battery and an electrical device comprising the same. The present invention and preferred embodiments are described in more detail below.
[0062] Binder composition
[0063] The "binder composition" referred to herein relates to a composition comprising at least two binders.
[0064] Specifically, the adhesive composition provided in the present application includes: a first adhesive and a second adhesive. In some embodiments, the adhesive composition consists of the first adhesive and the second adhesive.
[0065] Wherein, the first binder is a commonly used binder in the art, such as PTFE binder (homopolymer or copolymer with tetrafluoroethylene as monomer), PVDF binder (homopolymer or copolymer with vinylidene fluoride as monomer), modified PVDF binder (such as cyanate-modified polyvinylidene fluoride binder), polyacrylonitrile binder (homopolymer or copolymer with acrylonitrile as monomer), and styrene-butadiene rubber (SBR) and polyacrylamide (PAM), but not limited thereto. For example, considering the availability, PTFE, PVDF, etc. can be selected, for example, a binder with a molecular weight of 10000-100000000, optionally a binder with a molecular weight of 100000-800000000 can be selected, but not limited thereto.
[0066] When the bonding effect is exerted in the form of powder, the first binder provides linear bonding by fibrillation, so the bonding effect is achieved in a single manner. In this case, setting an "anchor point" in the linear adhesion will effectively improve the bonding effect, that is, including a specific second binder as defined in the present application in the binder composition.
[0067] The second binder includes a hyperbranched polymer obtained by polymerizing monomer A and monomer B, or a composition consisting of a plurality of the hyperbranched polymers.
[0068] In some embodiments, the monomer A contains two or more unsaturated carbon-carbon double bonds, and mainly serves as a branching center for generating a hyperbranched structure in the polymerization reaction. The monomer B contains one unsaturated carbon-carbon double bond, and provides a branched structure in the hyperbranched polymer.
[0069] More specifically, the monomer A comprises at least one of the compounds represented by general formula (I):
[0070]
[0071] Wherein, R1, R2, R3 are each independently selected from -H or -(OCH2CH2) n OC(O)CR 1a =CR 1b R 1c Right now R4 is selected from -H, -OH, -CH2OR 1a , -C1-C3 alkyl or -CH2(OCH2CH2) n OC(O)CR 1a =CR 1b R 1c ,Right now and R1, R2, and R3 are not all -H at the same time, and when two of R1, R2, and R3 are selected from -H, R4 is selected from Each R 1a , R 1b , R 1c Each is independently selected from -H, -C1-C4 alkyl, and n is an integer from 0 to 5. It should be understood that R1, R2, R3, and R4 may be the same or different, that is, for example, when R1, R2, R3, and R4 all refer to R 1a , R 1b , R 1c (For R4, only R 1a ), each R 1a Between each R 1b Between each R 1c can be the same or different, and R 1a , R 1b , R 1c Can be the same or different.
[0072] The monomer B includes at least one of the compounds represented by general formula (II):
[0073]
[0074] Wherein, Ra and Rb are each independently selected from -H, -C1-C3 alkyl, -COOR'; Rc is selected from -COOR', -CON(R')2 or Wherein R' is independently selected from -H, -C1-C6 alkyl, -(CH2) m -OH; m is an integer of 1 to 5.
[0075] In the binder composition of the present application, since the second binder used is a hyperbranched polymer (such as Figure 1 As shown schematically, it has a three-dimensional network structure, which is easy to distribute stress, making the force more uniform, and also gives the binder composition high elasticity, which is easy to process, is beneficial to the flexibility of the subsequent electrode, and buffers the volume change of the active material, thereby contributing to the integrity and stability of the electrode during long-term cycles.
[0076] Furthermore, the second adhesive has hyperbranched fulcrums, which produce point bonding during the bonding process. Therefore, the combination of the second adhesive and the first adhesive enables linear bonding and point bonding to cooperate and interact with each other during the bonding process to produce a synergistic bonding effect.
[0077] Furthermore, the second binder also includes a polar group, so that the binder composition has good electronegativity, which is beneficial to promote the formation of a conductive network and improve the power density of the electrode.
[0078] In some embodiments, R 1a , R 1b , R 1c Independently selected from H, methyl, ethyl, propyl or isopropyl, n can be 0, 1, 2, 3, 4 or 5.
[0079] In some embodiments, Ra and Rb are independently selected from H, methyl, ethyl, propyl, isopropyl, -COOR'; Rc is selected from -COOR', -CONH2, -CON(CH2CH3)2 or Wherein R' is independently selected from H, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, hexyl, -(CH2) m -OH; m can be 1, 2, 3, 4 or 5.
[0080] In some embodiments, in the general formula (I), R1, R2, and R3 are each independently selected from and R4 is selected from -OH, -CH2OR 1a 、-CH2CH3、 Each R 1a , R 1b , R 1c Each is independently selected from -H, -CH3 or -CH2CH3, and n is 0 or 1.
[0081] In some embodiments, R1, R2, and R3 are independently selected from H or Where R 1a , R 1b , R 1c are independently selected from H, methyl or ethyl, and n is 0 or 1. Optionally, R4 is -CH2OH, R1, R2, R3 are Where R 1a , R 1b , R 1c is independently selected from -H or methyl, and n is 0. Optionally, R4 is And R1, R2, R3 are Where n is 0 or 1, and R 1a , R 1b , R 1c All are H or methyl. Without wishing to be limited by theory, the monomers of the above-defined general formula (I) and general formula (II) can more easily obtain branched polymers with appropriate molecular weight, appropriate degree of branching and appropriate degree of dispersion through polymerization.
[0082] In some specific embodiments, monomer A may include at least one of pentaerythritol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, and ethoxylated pentaerythritol tetraacrylate. These monomer raw materials are all cheap and readily available, so that the second binder can be obtained at a relatively low cost, thus being suitable for large-scale commercial production.
[0083] In some embodiments, in the general formula (II), Ra is selected from -H; Rb is selected from -H, -C1-C3 alkyl; Rc is selected from -COOR' or wherein R' is selected from -H, -C1-C4 alkyl, -CH2OH or -CH2CH2OH.
[0084] In some embodiments, Ra is selected from -H, Rb is selected from -H or methyl, and Rc is selected from -COOH, -COOCH3, -COOC2H5, -COOC3H7, -COOC4H9, -COOCH2OH, -COOCH2CH2OH or Without wishing to be limited by theory, the monomers of the above-defined general formula (II) and general formula (I) can more easily obtain branched polymers with appropriate molecular weight, appropriate degree of branching and appropriate degree of dispersion through polymerization.
[0085] In some specific embodiments, monomer B may include one or more of acrylic acid, methacrylic acid, vinyl pyrrolidone, methyl methacrylate, ethyl methacrylate, propyl methacrylate, hydroxyethyl methacrylate, and butyl methacrylate. These monomer raw materials are all cheap and readily available, so that the second binder can be obtained at a relatively low cost, thus being suitable for large-scale commercial production.
[0086] In some embodiments, the molar ratio of the monomer A to the monomer B is 1:2-4, and can be 1:2-3. The molar ratio of the monomer A to the monomer B affects the viscosity, flexibility, etc. of the obtained branched polymer. When it is within the limited range of the present application, the obtained branched polymer has a low viscosity, is easy to process, and has moderate flexibility.
[0087] In some embodiments, the number average molecular weight of the second binder is 100,000 to 1,000,000. When the number average molecular weight of the binder is within this range, the branched polymer formed has a moderate degree of branching, and plays an effective point bonding role; and the viscosity is moderate, which is conducive to subsequent processing and production, especially to the formation of small particle size powder during spray drying. In other words, when the number average molecular weight of the polymer is within this range, the second binder has both excellent bonding strength and good flexibility.
[0088] In some embodiments, the second binder further satisfies at least one of conditions (1) to (3): (1) its corresponding emulsion viscosity is CmPa*s, 2500≤C≤15000; (2) glass transition temperature Tg℃, -50℃≤Tg≤20℃; (3) the crystallinity of the polymer under differential scanning calorimeter DSC test is less than <35%.
[0089] When the viscosity of the corresponding emulsion of the polymer of the present application is within the above range, it is easy to process and the corresponding polymer powder particles are easy to disperse. When the glass transition temperature of the polymer is within the above range, it can be easy to process and improve the flexibility of the formed pole piece, and enhance the mechanical properties of the pole piece. When the crystallinity of the polymer is within the above range, it will basically not affect the circulation of molecules in the electrolyte, and thus will not affect the charge and discharge performance of the battery.
[0090] In some embodiments, the mass ratio of the first binder to the second binder is (0.1-9.9):(9.9-0.1), and can be optionally (3-7):(7-3). The combination of the first binder and the second binder within this range can achieve a synergistic bonding effect between the fibrillated linear bonding of the first binder and the point bonding of the second binder itself, thereby improving the bonding strength and cohesion during pole piece molding.
[0091] In some embodiments, the binder composition is a powder binder. More specifically, the volume average particle size Dv50 of the binder composition is 5 μm to 50 μm, optionally 5 μm to 10 μm, such as 6, 7, 8, 9 μm. The powder form within this range can effectively combine the active material and the conductive material on the current collector, improve the compaction density, and simultaneously improve the surface capacity and the electrode gram capacity.
[0092] Preparation method
[0093] A second aspect of the embodiments of the present application provides a method for preparing an adhesive composition, which can prepare the adhesive composition of the first aspect of the embodiments of the present application.
[0094] The preparation method of the binder composition comprises the following steps:
[0095] providing a first adhesive;
[0096] polymerizing a mixture including monomer A and monomer B to obtain a second binder; and
[0097] mixing the first binder and the second binder;
[0098] Wherein, the second binder comprises a hyperbranched polymer obtained by polymerization of monomer A and monomer B;
[0099] Wherein, the monomer A comprises at least one of the compounds represented by general formula (I):
[0100]
[0101] Wherein, R1, R2, R3 are each independently selected from -H or R4 is selected from -H, -OH, -CH2OR 1a , -C1-C3 alkyl or and R1, R2, and R3 are not all -H at the same time, and when two of R1, R2, and R3 are selected from -H, R4 is selected from Each R 1a , R 1b , R 1c Each is independently selected from -H or -C1-C4 alkyl, and n is an integer from 0 to 5;
[0102] The monomer B includes at least one of the compounds represented by general formula (II):
[0103]
[0104] Wherein, Ra and Rb are each independently selected from -H, -C1-C3 alkyl or -COOR'; Rc is selected from -COOR', -CON(R')2 or Wherein R' is independently selected from -H, -C1-C6 alkyl or -(CH2) m -OH; m is an integer of 1 to 5.
[0105] More specifically, monomer A and monomer B have the same definitions as in the first aspect of the embodiment of the present application. The preparation method of the present invention is easy to operate and environmentally friendly.
[0106] In some embodiments, polymerizing a mixture including monomer A and monomer B to obtain a second binder includes: adding monomer A and monomer B to a solvent, then adding a catalyst under stirring, and reacting the mixture under an inert environment to obtain a reaction emulsion; then drying the reaction emulsion in a spray drying machine and pulverizing it to obtain a powder of the second binder. The binder is prepared by free radical polymerization, and the polymerization speed is fast; after the reaction reaches a high conversion rate, the viscosity of the emulsion system is still very low, the dispersion system is stable, and it is easier to control and realize continuous operation.
[0107] In some embodiments, the solvent used may be water.
[0108] In some embodiments, monomer A and monomer B may be dissolved in solvents respectively, and then the solution including monomer B may be added dropwise or in batches to the solution including monomer A.
[0109] In some embodiments, the polymerization of monomer A and monomer B may be performed under one or more of the following conditions: ultraviolet light, heating, and radiation, but is not limited thereto.
[0110] In some embodiments, the inert environment may be a nitrogen environment, but is not limited thereto.
[0111] In some embodiments, the catalyst may include one or more selected from sulfur dioxide, sulfur trioxide, and disulfur trioxide.
[0112] In some embodiments, the spray drying may be performed at a temperature of 150°C to 200°C, such as 160°C, 170°C, 180°C, or 190°C.
[0113] The reaction conditions of the preparation method of the present application are mild and controllable, which is conducive to the continuous production of the binder composition of the present application.
[0114] In some embodiments, mixing the first binder and the second binder includes: at a temperature below 20°C (such as, 19°C, 15°C, 10°C, etc., but not limited thereto), fully mixing the powder of the second binder with the first binder to obtain the binder composition.
[0115] Next, the battery and the electric device of the present application will be described with reference to the accompanying drawings.
[0116] Battery
[0117] In one embodiment of the present application, a battery is provided.
[0118] The term "battery" mentioned in this article refers to a battery cell, a battery module or a battery pack. Each of these is described below.
[0119] Generally, a battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0120] [Positive electrode]
[0121] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the binder composition of the first aspect of the present application or the binder composition prepared according to the method of the second aspect of the present application.
[0122] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0123] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0124] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0125] When the battery cell is a sodium ion battery, the positive electrode active material may include at least one of a sodium transition metal oxide, a polyanionic compound and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0126] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, 0 <x≤1。
[0127] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence state.
[0128] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y may be at least one of P, S and Si, and n represents (Y04) n- valence state; the halogen may be at least one of F, Cl and Br.
[0129] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n- Valence state: Z represents a transition metal, which can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce, and m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.
[0130] Polyanionic compounds include NaFePO4, Na3V2(PO4)3, NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).
[0131] The Prussian blue compound may be a compound having sodium ions, transition metal ions and cyanide ions (CN-). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The Prussian blue compound may be, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0 <a≤2,0<b<1,0<c<1。
[0132] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0133] In the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0134] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0135] In some embodiments, the positive electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder composition of the present application and any other components are mixed and rolled multiple times on a roller press to obtain a positive electrode film; the positive electrode film is placed on the positive electrode collector, and after calendering and other processes, the positive electrode sheet can be obtained.
[0136] [Negative electrode]
[0137] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material and the binder composition of the first aspect of the present application or the binder composition prepared according to the method of the second aspect of the present application.
[0138] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0139] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0140] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0141] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0142] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0143] In some embodiments, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder composition of the present application and any other components are mixed and rolled multiple times on a roller press to obtain a negative electrode film; the negative electrode film is placed on a negative electrode collector, and after calendering and other processes, the negative electrode sheet can be obtained.
[0144] [Electrolytes]
[0145] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0146] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0147] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0148] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0149] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0150] [Isolation film]
[0151] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0152] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0153] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0154] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0155] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0156] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.
[0157] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0158] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0159] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0160] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0161] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0162] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0163] Electrical devices
[0164] In addition, another aspect of the present application provides an electrical device.
[0165] The electrical device includes the battery provided in the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0166] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0167] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the battery, a battery pack or a battery module can be used.
[0168] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0169] Example
[0170] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0171] Preparation of the second binder
[0172] Preparation Example 1
[0173] Pentaerythritol triacrylate was dispersed in water, and then vinyl pyrrolidone dissolved in an appropriate amount of water was added dropwise, wherein the molar ratio of pentaerythritol triacrylate to vinyl pyrrolidone was 1:2. After the mixture was stirred uniformly at 250 r / min, sulfur dioxide was added as a catalyst, and ultraviolet light was applied at the same time to promote the reaction, and a polymer emulsion was obtained after reacting for 3 hours in a nitrogen environment.
[0174] The obtained emulsion was dried at 150° C. in a spray dryer and simultaneously pulverized into particles using a jet mill to obtain a hyperbranched polymer powder binder with a particle size of 5 μm.
[0175] Preparation Examples 2 to 7
[0176] Preparation Examples 2 to 7 were carried out in the same manner as Preparation Example 1 according to the parameters shown in Table 1 below.
[0177] Table 1. Relevant parameters of preparation examples 1 to 7
[0178]
[0179] Characterization of the Second Binder
[0180] Emulsion viscosity measurement
[0181] The polymer emulsions obtained in Preparation Examples 1 to 7 were tested by Brookfield DV2T viscometer at room temperature 25° C. and relative humidity RH<80% to obtain viscosity values. The results are shown in Table 2 below.
[0182] Number average molecular weight
[0183] The number average molecular weights of the hyperbranched polymer powder binders obtained in Preparation Examples 1 to 7 were measured by gel permeation chromatography (GPC). The results are shown in Table 2 below.
[0184] Glass transition temperature (Tg) and crystallinity
[0185] The glass transition temperature (Tg) and crystallinity of the hyperbranched polymer powder binders obtained in Preparation Examples 1 to 7 were measured by differential thermal analysis (DSC) (NETZSCH / DSC200F3 / STA449F3).
[0186] Table 2. Characteristic parameters of branched polymers obtained in Preparation Examples 1 to 7
[0187] project Number average molecular weight Glass transition temperature / ℃ Crystallinity Corresponding emulsion viscosity / mPa·s Preparation Example 1 150000 -24 <5% 5000 Preparation Example 2 180000 -20 12% 7000 Preparation Example 3 130000 10 15% 2500 Preparation Example 4 500000 -15 7% 10000 Preparation Example 5 830000 -8 23% 10300 Preparation Example 6 420000 -3 32% 7900 Preparation Example 7 700000 5 17% 15000
[0188] Preparation of adhesive composition
[0189] Example 1-11: The second binder prepared in Preparation Examples 1 to 7 was mixed with the first binder of the corresponding particle size at a weight ratio shown in Table 3 at 3000 r / min for 30 min at low temperature (below 20°C) to obtain a powder mixture, wherein the powder had no agglomeration phenomenon. The PVDF used was purchased from Arkema Chemical (model POWER FLEX LBG FSFPWD), PTFE was purchased from Daikin Chemical (model 104), SBR was purchased from Japan Co., Ltd. (Mw about 200000, Tg = -57°C), and PAN was purchased from Aladdin Reagent Platform (Mw about 150000, Tg = 83°C)
[0190] In addition, according to the compositions and weight ratios in Table 3 below, binders of Comparative Examples 1 to 8 were prepared.
[0191] Table 3
[0192] project First binder Second binder Weight Ratio Powder particle size (μm) Example 1 PVDF Preparation Example 1 0.1:9.9 5 Example 2 PVDF Preparation Example 1 9.9:0.1 5 Example 3 PVDF Preparation Example 1 3:7 5 Example 4 PVDF Preparation Example 1 7:3 5 Example 5 PVDF Preparation Example 1 5:5 5 Example 6 PVDF Preparation Example 5 5:5 20 Example 7 PVDF Preparation Example 6 5:5 10 Example 8 PVDF Preparation Example 7 5:5 7 Example 9 PTFE Preparation Example 2 4:6 10 Example 10 SBR Preparation Example 3 6:4 50 Embodiment 11 PAN Preparation Example 4 3:7 5 Comparative Example 1 PVDF none / 5 Comparative Example 2 PVDF PTFE 3:7 5 Comparative Example 3 none Preparation Example 1 / 5 Comparative Example 4 Preparation Example 1 Preparation Example 4 7:3 5 Comparative Example 5 PAN none / 5 Comparative Example 6 none Preparation Example 4 / 5 Comparative Example 7 PAN SBR 3:7 5 Comparative Example 8 Preparation Example 1 Preparation Example 4 3:7 5
[0193] Preparation of pole piece
[0194] Preparation of positive electrode sheets: The binder compositions of Examples 1 to 9 and the binders of Comparative Examples 1 to 4 were respectively mixed with lithium iron phosphate and conductive carbon black at a weight ratio of 1:8:1 at 3000 r / min for 3 h, and then rolled multiple times on a roller press to obtain positive electrode sheets.
[0195] The obtained positive electrode film is laminated on aluminum foil and subjected to multiple hot roller rolling to obtain the final positive electrode sheet.
[0196] Preparation of negative electrode sheets: The binders of Examples 10 to 11 and Comparative Examples 5 to 8 were uniformly stirred with graphite and conductive carbon black at a weight ratio of 1:8:1 at 3000 r / min for 3 h, and then rolled multiple times on a roller press to obtain negative electrode membranes.
[0197] Subsequently, the obtained negative electrode film is laminated on a copper foil and subjected to multiple hot roller rolling to obtain a final negative electrode sheet.
[0198] Characterization of positive electrode performance
[0199] The positive electrode sheets prepared in Examples 1 to 9 and Comparative Examples 1 to 4 were subjected to a sheet peeling strength test.
[0200] The peel strength test is as follows:
[0201] Refer to GB-T 2790-1995 national standard "Adhesive 180° Peel Strength Test Method", use a blade to cut a sample with a width of 30mm and a length of 100-160mm, and stick the special double-sided tape on the steel plate, the tape width is 20mm, and the length is 90-150mm. Stick the positive electrode film layer of the electrode sample cut earlier on the double-sided tape, and then roll it three times in the same direction with a 2kg roller. Fix a paper tape with a width equal to the electrode and a length of 250mm on the electrode collector and fix it with wrinkled glue. Turn on the power of the Sansi tensile machine (sensitivity is 1N), the indicator light is on, adjust the limit block to the appropriate position, and fix the end of the steel plate without the electrode with the lower clamp. Fold the paper tape upwards and fix it with the upper clamp, and use the "up" and "down" buttons on the manual controller attached to the tensile machine to adjust the position of the upper clamp. Then test and read the value in N / m. The results are shown in Table 4 below.
[0202] Characterization of negative electrode performance
[0203] Adhesion test and cohesion test were performed on the negative electrode sheets prepared in Examples 10-11 and Comparative Examples 5-8.
[0204] Adhesion test
[0205] Stick the double-sided tape on the steel plate. The tape should be 20mm wide and 90mm long.
[0206] Use a blade to cut a 30mm wide and 90mm long electrode to be tested. Then stick it on the double-sided tape with the test side facing up. Use a roller to roll it three times in the same direction.
[0207] Turn on the power of the tensile testing machine (Zhongzhi Testing Tensile Testing Machine, Model LXG2-LLCS-0009), fix the end of the steel plate without the electrode with the lower clamp, ensure that the steel plate is placed vertically with the base, and the bottom of the steel plate is flush with the base. Fold the electrode attached to the steel plate upwards and fix it with the upper clamp.
[0208] First pre-stretch about 5mm, then "clear" the "force" and "displacement" parameters, and after the above two parameters are reset to zero, click the start button to start the test, and then record the test results. Then do three groups in parallel, and calculate the average value N1 (unit: N / 20mm), and the final bonding force size = N1*50.
[0209] The resulting data are shown in Table 4 below.
[0210] Cohesion test
[0211] Stick the double-sided tape on the steel plate. The tape should be 20mm wide and 90mm long.
[0212] Use a blade to cut off the electrode to be tested with a width of 30mm and a length of 90mm. Then stick it on the double-sided tape with the test surface facing up. Stick a low-viscosity green tape with a width of 20mm and a length greater than the length of the tape evenly on the surface of the test surface, and roll it three times in the same direction with a roller.
[0213] Turn on the power of the tensile testing machine, fix the end of the steel plate without the electrode with the lower clamp, ensure that the steel plate is placed vertically with the base, and the bottom of the steel plate is flush with the base. Fold the green glue with the hard paper upwards and fix it with the upper clamp.
[0214] First pre-stretch about 5mm, then "clear" the "force" and "displacement" parameters, and after the above two parameters are reset to zero, click the start button to start the test, and then record the test results. Then do three groups in parallel, and calculate the average value N1 (unit: N / 20mm), and the final cohesive force size = N1*50.
[0215] The resulting data are shown in Table 4 below.
[0216] Table 4. Relevant test results of Examples 1 to 11 and Comparative Examples 1 to 8
[0217]
[0218]
[0219] It can be seen from Table 4 above that the peel strength of the positive electrode membranes of Examples 1 to 9 is greatly improved compared with Comparative Examples 1 to 4. Specifically, relative to the first binder (e.g., Comparative Example 1) or the second binder (e.g., Comparative Example 3) used alone and relative to the combination of the first binder (e.g., Comparative Example 2) or the combination of the second binder (e.g., Comparative Example 4), the binder composition of the present application greatly improves the peel strength of the positive electrode membrane.
[0220] Similarly, the adhesive force and cohesive force of the negative electrode membranes of Examples 10 and 11 are also significantly improved compared to Comparative Examples 5 to 8. Without wishing to be bound by theory, it is believed that the above improvement can be attributed to the fact that when the binder that exerts a "linear" adhesive force and the binder that exerts a "point-like" adhesive force work together, the two cooperate with each other to produce a synergistic adhesive effect.
[0221] Preparation of secondary batteries (full batteries)
[0222] Electrolyte: Lithium salt LiPF6 is added to a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a mass ratio of 35:65, and mixed evenly to obtain an electrolyte, wherein the molar concentration of LiPF6 in the electrolyte is 1 mol / L.
[0223] The positive electrode sheet, the 12 μm thick polyethylene porous film as the separator, and the negative electrode sheet are stacked in order, so that the separator is located between the positive and negative electrodes to play a role of isolation, and the electrode assembly is obtained by winding. The electrode assembly is placed in an outer package, injected with the above-prepared electrolyte and packaged, and the lithium ion battery application examples 1-11 and battery application comparative examples 1-7 are obtained through the process of formation, degassing, trimming, etc.
[0224] Among them, in battery application examples 1-9, the positive electrode sheet is the positive electrode sheet prepared in examples 1-9, and the negative electrode sheet is the negative electrode sheet prepared in comparative example 5 (the binder is PAN); in battery application examples 10-11, the positive electrode sheet is the positive electrode sheet prepared in comparative example 1 (the binder is PVDF), and the negative electrode sheet is the negative electrode sheet prepared in examples 7-8;
[0225] In battery application comparative examples 1-4, the positive electrode sheet is the positive electrode sheet prepared in comparative examples 1-4, and the negative electrode sheet is the negative electrode sheet prepared in comparative example 5 (the binder is PAN); in battery application comparative examples 5-7, the positive electrode sheet is the positive electrode sheet prepared in comparative example 1 (the binder is PVDF), and the negative electrode sheet is the negative electrode sheet prepared in comparative examples 6-8.
[0226] Performance measurement
[0227] Cycle capacity
[0228] At 25℃ / 45℃, the battery was charged to 4.35V at a constant current of 1C, then charged at a constant voltage of 4.35V until the current dropped to 0.05C, and then discharged to 2.5V at a constant current of 1C to obtain the first cycle discharge capacity (C0). This was repeated until the 500th cycle, and the discharge capacity after 500 cycles was obtained, recorded as C n .
[0229] Capacity retention rate = discharge capacity after 500 cycles (C n The results are shown in Table 5.
[0230] Table 5. Test results
[0231] project 25℃ capacity retention rate 45℃ capacity retention rate Battery Application Example 1 97% 87% Battery Application Example 2 96% 86% Battery Application Example 3 97% 89% Battery Application Example 4 98% 89% Battery Application Example 5 98% 90% Battery Application Example 6 97% 88% Battery Application Example 7 97% 89% Battery Application Example 8 98% 90% Battery Application Example 9 98% 86% Battery Application Example 10 96% 86% Battery Application Example 11 98% 89% Battery Application Comparative Example 1 94% 80% Battery Application Comparative Example 2 92% 78% Battery Application Comparative Example 3 93% 83% Battery Application Comparative Example 4 92% 81% Battery Application Comparative Example 5 93% 80% Battery Application Comparative Example 6 93% 82% Battery Application Comparative Example 7 92% 81%
[0232] It can be seen from Table 5 above that when the binder composition of the present application is applied to the positive electrode sheet, compared with the first binder used alone (for example, battery application comparative example 1) and the first binder used in combination (for example, battery application comparative example 2), and the second binder used alone (for example, battery application comparative example 3) and the second binder used in combination (for example, battery application comparative example 4), the battery application examples 1 to 9 of the present application achieve an improvement in the cycle capacity retention rate at 25°C and the cycle capacity retention rate at 45°C. Similarly, when the binder composition of the present application is applied to the negative electrode sheet, the cycle capacity retention rate at 25°C and 45°C is also improved. This also indirectly reflects the stability of the electrode in the battery, which is attributed to the good bonding strength of the binder and the suppression of the expansion of the electrode at high temperature.
[0233] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A binder composition comprising: a first binder; as well as A second binder, wherein the second binder comprises a hyperbranched polymer obtained by polymerization of monomer A and monomer B; Wherein, the monomer A comprises at least one of the compounds represented by general formula (I): Wherein, R1, R2, R3 are each independently selected from -H or R4 is selected from -H, -OH, -CH2OR 1a , -C1-C3 alkyl or and R1, R2, and R3 are not all -H at the same time, and when two of R1, R2, and R3 are selected from -H, R4 is selected from Each R 1a , R 1b , R 1c Each is independently selected from -H or -C1-C4 alkyl, and n is an integer from 0 to 5; The monomer B includes at least one of the compounds represented by general formula (II): wherein Ra and Rb are each independently selected from -H, -C1-C3 alkyl or -COOR'; Rc is selected from -COOR', -CON(R')2 or Wherein R' is independently selected from -H, -C1-C6 alkyl or -(CH2) m -OH; m is an integer of 1 to 5.
2. The adhesive composition according to claim 1, characterized in that In the general formula (I), R1, R2, and R3 are each independently selected from and R4 is selected from -OH, -CH2OR 1a , -CH2CH3 or Each R 1a , R 1b , R 1c Each is independently selected from -H, -CH3 or -CH2CH3, and n is 0 or 1.
3. The adhesive composition according to claim 1 or 2, characterized in that: In the general formula (II), Ra is selected from -H; Rb is selected from -H or -C1-C3 alkyl; Rc is selected from -COOR' or wherein R' is selected from -H, -C1-C4 alkyl, -CH2OH or -CH2CH2OH.
4. The adhesive composition according to any one of claims 1 to 3, characterized in that The monomer A includes at least one of pentaerythritol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate or ethoxylated pentaerythritol tetraacrylate.
5. The adhesive composition according to any one of claims 1 to 4, characterized in that The monomer B includes at least one of acrylic acid, methacrylic acid, N-vinyl pyrrolidone, methyl methacrylate, ethyl methacrylate, propyl methacrylate, hydroxyethyl methacrylate or butyl methacrylate.
6. The adhesive composition according to any one of claims 1 to 5, characterized in that The molar ratio of the monomer A to the monomer B is 1:2-4, and can be optionally 1:2-3.
7. The binder composition according to any one of claims 1 to 6, characterized in that The number average molecular weight of the second binder is 100,000 to 1,000,000.
8. The adhesive composition according to any one of claims 1 to 7, characterized in that The first adhesive includes at least one of a PTFE adhesive, a PVDF adhesive, a modified PVDF adhesive, a polyacrylonitrile adhesive, styrene-butadiene rubber or polyacrylamide.
9. The adhesive composition according to any one of claims 1 to 8, characterized in that The mass ratio of the first binder to the second binder is (0.1-9.9):(9.9-0.1), and can be optionally (3-7):(7-3).
10. The adhesive composition according to any one of claims 1 to 9, characterized in that The volume average particle size Dv50 of the binder composition is 5 μm-50 μm, and can be optionally 5 μm-10 μm.
11. A method for preparing a binder composition, comprising: providing a first adhesive; polymerizing a mixture including monomer A and monomer B to obtain a second binder; as well as mixing the first binder and the second binder; Wherein, the second binder comprises a hyperbranched polymer obtained by polymerization of monomer A and monomer B; Wherein, the monomer A comprises at least one of the compounds represented by general formula (I): Wherein, R1, R2, R3 are each independently selected from -H or R4 is selected from -H, -OH, -CH2OR 1a , -C1-C3 alkyl or and R1, R2, and R3 are not all -H at the same time, and when two of R1, R2, and R3 are selected from -H, R4 is selected from Each R 1a , R 1b , R 1c Each is independently selected from -H or -C1-C4 alkyl, and n is an integer from 0 to 5; The monomer B includes at least one of the compounds represented by general formula (II): wherein Ra and Rb are each independently selected from -H, -C1-C3 alkyl or -COOR'; Rc is selected from -COOR', -CON(R')2 or Wherein R' is independently selected from -H, -C1-C6 alkyl or -(CH2) m -OH; m is an integer of 1 to 5.
12. The preparation method according to claim 11, characterized in that: The first adhesive includes at least one of a PTFE adhesive, a PVDF adhesive, a modified PVDF adhesive, a polyacrylonitrile adhesive, styrene-butadiene rubber or polyacrylamide.
13. An electrode plate, comprising: A current collector and an electrode film layer disposed on at least one side of the current collector, wherein the electrode film layer comprises the binder composition according to any one of claims 1 to 10 or the binder composition obtained by the preparation method according to claim 11 or 12.
14. The electrode plate according to claim 13, characterized in that: The electrode plates are positive electrode plates and / or negative electrode plates.
15. A battery comprising the electrode sheet according to claim 13 or 14.
16. An electrical device comprising the battery according to claim 15.